Motif and Dynamics of Women in Assault Crimes: An Empirical Study at the Gorontalo Resort Police - Abdulah, Nadia Rahmatiya; U. Puluhulawa, Moh. Rusdiyanto; Rivadi Moha, Mohamad; Khairunnisa, Riska (Estudiante Law Journal, 2025)
The criminal act of abuse committed by women is an intriguing phenomenon to study, particularly in the context of social dynamics and gender roles that influence such actions. This research aims to delve deeper into the factors that drive women to commit violence, as well as the countermeasures implemented by the Gorontalo Police Resort to address this issue. The methodology employed in this study is a qualitative approach with empirical analysis, involving in-depth interviews with law enforcement officers, victims, and perpetrators of violence. Data was also gathered through document studies, including case reports of criminal abuse involving women as perpetrators. The findings reveal that criminal abuse by women is often triggered by emotional factors such as heartache, anger, as well as social and economic pressures. Furthermore, past experiences of violence also contribute to violent behavior in adulthood. In terms of intervention, the Gorontalo Police Resort applies a three-stage approach: preemptive, preventive, and repressive. This approach includes public education, support for victims, and strict law enforcement against perpetrators. Rehabilitation for perpetrators of violence is also an essential part of long-term efforts to prevent recurring violence. This study is expected to contribute to the development of more effective policies aimed at reducing gender-based violence.